Dental morphology analysis of afro-colombian schoolchildren from Villa Rica, Cauca, Colombia - Marcovich, Isabella; Prado, Eliana; Díaz, Paola; Ortiz, Yenny; Martínez, Carlos; Moreno, Freddy (Revista Facultad de Odontología Universidad de Antioquia, 2012)
Introduction: the study of dental morphology allows establishing the evolutionary state (biological distance and crossbreeding status) of a community, offering information on its ethno-historical processes (in this case a Colombian population) within the anthropological, dental, and forensic contexts. Methods: this was a quantitative, transversal, descriptive study with the intention of establishing dental morphology by means of the Asudas system (Arizona State University Dental Anthropology System) based on thirteen crown morphologic dental traits (winging, crowding, shovel-shaped central incisors, shovel-shaped lateral incisors, double shoveling, Carabelli’s cusp, hypocone reduction, deflecting wrinkle, protostylid, cusp pattern, cusp number, cusp 6, and cusp 7) Results: significant frequencies of these traits were observed: Carabelli’s cusp, configuration of cuspid patterns X5 and X6 (LM1) and +4 and +5 (LM2), absence of hypocone reduction, relative frequency of cusp 7, and low frequencies of shovel-shaped incisors and double shoveling. It may also be stated that the studied crown morphologic dental traits (CMDT) do not show sexual dimorphism or bilateral asymmetry. Conclusions: the analyzed sample shows a dental morphology typical of populations of the Caucasoid dental complex; however, the influence of Mongoloid groups and biological affinities with Caucasoid mestizo groups and Afro-Colombian populations is also evident.